Pengaruh Pengeluaran Pembangunan dan Investasi terhadap Pertumbuhan Ekonomi Provinsi Sumatera Utara - Raihan Mubarak; Aditya Effendi; Ahmad Wahyudi Zein (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
Economic growth measures the achievement of the development of an economy from one period to the next. Theoretically, government spending allocated for the public interest and public welfare will encourage an increase in per capita income that is getting bigger from year to year. Investment is essentially also the initial step in economic development activities. This study aims to determine the Effect of Development Spending and Investment on Economic Growth in North Sumatra Province. The analysis technique used is data analysis in this study using a descriptive analysis method based on the descriptions that support the analysis. The results of this study indicate that partially the government spending variable has a significant negative effect on economic growth in North Sumatra Province with a significance value of 0.0030.05. Based on the results of the simultaneous test calculation, it is known that both government spending and investment variables simultaneously have a positive and significant effect on economic growth in North Sumatra Province with a significance value of 0.030.